Industrial system analysis and design study on Union Refinery Corporation - Pariño, Maria Karren (College of Engineering, 2004)
Union Refinery Corporation (URC) is the production arm of one of the major petroleum product supplier in the Philippines, which is Unioil Petroleum Philippines, Inc. It is involved in the blending, filling and development processes of lubricants and other specialty oils for the said company. URC has also been a highly reliable supplier of a wide range of automotive and industrial lubricants as well as process oils, base oils and other fuel oils. With the existence of Shell, Petron, and Caltex as the dominant player in the industry, the challenge for Union Refinery Corporation has been continuously increasing. This study aims to devise a system that would improve the company's performance in the market in order to be competitive enough as a realization of its vision to be a dominant lubricant player with a passion for providing excellent products and services. Upon performance of SWOT Analysis and studying the company's Porter's Five Forces Model, it was recommended that an expansion plan be pursued. This is to accommodate the unutilized capacity of the plant. However, it must be noted that a pre-feasibility study be done in order to achieve more accurate results. From the Problem Analysis on URC, it was noted that three major problems are existent, namely, an inefficient inventory system for its imported raw materials, an inefficient material flow in the facility during production, and the short amount of time for the workers to progress in the learning curve. In the effort to address the problem on the inventory system, it was recommended that a Reorder point of 109,463.1 liters and a Reorder Quantity of 160,000 liters be employed. As for the problem in the material flow, a proposed layout of the facility is presented. And finally, a practical training was deemed to be beneficial for the newly-hired workers in order to give them leverage in their new job. With the implementation of these recommendations, it was estimated that a total annual savings of Php 644,853.90 would be incurred by the company. Further these recommendations were geared toward the fulfillment of the Mission Statement. Marketing strategies would be generated with the pushing through of the expansion plan for UPPI. Processes were re-aligned and operational excellence was achieved by empowering the workers and by revising the layout in order to minimize the material flow in the facility. Moreover, by minimizing the material flow, spillage and contamination will be prevented and thus produce competitive products. Finally, with the new Reorder Point and Reorder Quantity, stock-outs will be minimized and deadlines will be met thus winning customer loyalty.